Component of motor vehicle or motorcycle comprising titanium dioxide-based coating
By using a colloidal solution coating made of TiO2 inorganic precursor on automotive and motorcycle braking system components, dirt deposition and corrosion problems are solved, and self-cleaning and photocatalytic effects are achieved, suitable for details and performance requirements of high-end vehicles. .
Patent Information
- Application Number
- CN202380026757.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-11
- Filing Date
- 2023-03-09
- Publication Date
- 2025-01-03
AI Technical Summary
Braking system components of cars and motorcycles are susceptible to the deposition of dust, mud and harmful dirt, resulting in aesthetic damage and corrosion, especially in high-end vehicles, a technology that effectively reduces dirt adhesion and protects surfaces.
Using a colloidal solution obtained by hydrolysis and condensation reaction between TiO2 inorganic precursor and water as a coating, it is applied to a metal substrate through a sol-gel process, providing self-cleaning properties and photocatalytic activity to enhance the sand and The repulsion of soil.
The self-cleaning characteristics and high adhesion of the metal substrate are realized, which significantly reduces dirt adhesion, maintains the surface transparency and anti-fouling performance, and demonstrates the photocatalytic activity against organic dirt.
Smart Images

Figure BDA0005036465190000121 
Figure BDA0005036465190000122 
Figure HDA0005036465200000011
Abstract
Description
Technical Field
[0001] The present invention relates to a component of an automobile or motorcycle, in particular a brake caliper or a brake disc, comprising a metal substrate and a coating comprising TiO2 for said substrate. The invention also relates to the use of a coating comprising TiO2 for imparting self-cleaning properties to a metal substrate to which said coating is applied. Background Art
[0002] In the automotive field, the problem of the deposition of dust, dirt and dirt on metal parts of vehicles in general and on metal parts of the vehicle's brake system, such as calipers and brake discs in particular, is strongly felt.
[0003] Natural exposure to the environment affects the appearance of these parts. In fact, the accumulation of mud during vehicle use and the deposition of dust during periods when the vehicle is stopped or parked can impair the aesthetics of the parts themselves. In addition, contamination caused by organic compounds can damage the finish of these parts through phenomena such as sandblasting and decorative oxidation.
[0004] The accumulation of dirt is not just an aesthetic problem. The adsorption of water, oxygen or corrosive ions can trigger corrosion processes and thus damage the component itself.
[0005] The above problems are most evident in luxury and high-performance vehicles such as high-end cars or racing bikes, for which greater attention to detail and performance is paid.
[0006] The problem underlying the present invention is therefore to solve the above-mentioned problem of providing a coating for components of automobiles and motorcycles, in particular for components of brake systems of automobiles and motorcycles, which coating is able to reduce the adhesion of dust, dirt and other harmful elements, thus keeping the components free of dirt and protecting the surface of the components from the influence of invasive cleaning procedures. Summary of the invention
[0007] The above mentioned problem is solved by a component for a car or motorcycle, a method for producing said component and the use of a sol-gel coating for imparting self-cleaning properties to a metal substrate to which this coating is applied, as outlined in the appended claims, the definitions of which form an integral part of the present description.
[0008] A first object of the present invention is to provide a component for an automobile or motorcycle, comprising a metal substrate and a coating for said substrate, wherein said coating comprises TiO2 and can be obtained by a sol-gel process, said sol-gel process comprising the steps of applying a colloidal solution to the metal substrate of said component for an automobile or motorcycle,
[0009] The colloidal solution is obtained by hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water.
[0010] The inorganic precursor of TiO2 has a molecular formula Ti(X)4, wherein the X group is a hydrolyzable group selected from halogen, -OR alkoxy group, and -COOR acyloxy group, and the X groups are the same or different from each other, wherein R is preferably a C1-C6 alkyl group.
[0011] The second object of the present invention is to provide a method for producing the above-mentioned parts of an automobile or motorcycle, the method comprising the following steps:
[0012] Providing a component including a metal substrate for an automobile or a motorcycle,
[0013] applying a colloidal solution obtained by hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water to the metal substrate,
[0014] The inorganic precursor of TiO2 has a molecular formula Ti(X)4, wherein the X group is a hydrolyzable group selected from halogen, -OR alkoxy group and -COOR acyloxy group, and the X groups are the same or different from each other, wherein R is preferably a C1-C6 alkyl group.
[0015] Another object of the present invention is to provide a use of a coating that can be obtained by the above method, which coating is used to provide self-cleaning properties to a metal substrate applied with the coating, in particular, the coating is used to provide self-cleaning properties to a metal substrate of an automobile or motorcycle part, preferably, the substrate is made of aluminum or an aluminum alloy; or, the substrate is made of iron or an iron alloy, for example, the substrate is made of steel or cast iron; or, the substrate is made of titanium or a titanium alloy.
[0016] Another object of the present invention is to provide a use of a colloidal solution as a coating for a metal substrate, the colloidal solution being used to provide the coating with self-cleaning properties, in particular, the coating for the metal substrate is a coating for a metal substrate of an automobile or motorcycle part, wherein the colloidal solution is obtained by a hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water,
[0017] The inorganic precursor of TiO2 has a molecular formula Ti(X)4, wherein the X group is a hydrolyzable group selected from halogen, -OR alkoxy group, and -COOR acyloxy group, and the X groups are the same or different from each other, wherein R is preferably a C1-C6 alkyl group.
[0018] The component according to the invention advantageously exhibits self-cleaning properties.
[0019] Further characteristics and advantages of the invention will become apparent from the following description of some embodiments given by way of non-limiting indication. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Photographs of an AlSi7 alloy substrate to which a coating comprising TiO 2 according to the invention was applied are shown before (A) and after (B) an adhesion test according to standard ASTM D3359.
[0021] Figure 2 is a graph showing the UV-visible degradation rate of methylene blue dye on an AlSi7 alloy substrate coated with TiO2 according to the present invention compared with the UV-visible degradation rate of methylene blue dye on an uncoated AlSi7 alloy substrate. DETAILED DESCRIPTION
[0022] The present invention relates to a component of an automobile or motorcycle, the component comprising a metal substrate, and a coating comprising TiO2 for the substrate, wherein the coating is obtained from an inorganic precursor of TiO2 by a sol-gel process. More particularly, the process comprises the step of applying a colloidal solution obtained by a hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water to the metal substrate.
[0023] It has been observed that the component according to the invention has self-cleaning properties, exhibiting photocatalytic activity towards organic dirt and a stronger repellency towards sand and dirt, which are more difficult to adhere to the coated metal substrate of the component.
[0024] Furthermore, the coatings described above surprisingly exhibit high adhesion to the metal substrates to which they are applied. The coatings also exhibit high levels of transparency without causing significant changes in the color of the substrates to which they are applied, an effect that cannot be ignored in the automotive sector.
[0025] The sol-gel process involves the synthesis of a colloidal solution, called a sol, which forms a precursor for the subsequent formation of an inorganic lattice, called a gel, through hydrolysis and condensation reactions.
[0026] The term "colloidal solution" used in the present application refers to a product obtained by a hydrolysis and condensation reaction between the above-mentioned inorganic precursor of TiO2 and water.
[0027] The inorganic precursor of TiO2 has a molecular formula Ti(X)4, wherein the X group is a hydrolyzable group selected from -OR alkoxy groups, -COOR acyloxy groups and halogens, and the X groups may be the same or different from each other. Preferably, R is a C1-C6 alkyl group, and the halogen is preferably Cl, Br and I.
[0028] Preferably, the X group is an -OR alkoxy group, wherein R is selected from methyl, ethyl, propyl and butyl. More preferably, the X group is an -OR alkoxy group, wherein R is selected from isopropyl and n-butyl.
[0029] Preferably, the inorganic precursor of TiO2 is titanium tetraalkoxide (also called tetraalkyl titanate), preferably, titanium tetraalkoxide has four alkoxy groups equal to each other. Preferably, the inorganic precursor of TiO2 is titanium n-butoxide (TNBT) or titanium isopropoxide (TTIP, titanium isopropoxide).
[0030] According to different embodiments, the colloidal solution can be obtained by reacting the inorganic precursor of TiO2 and water in the presence of a catalyst for hydrolysis or condensation reaction or in the presence of a chelating agent. The colloidal solution obtained using the catalyst is hereinafter referred to as "colloidal solution No. 1"; the colloidal solution obtained using the chelating agent is hereinafter referred to as "colloidal solution No. 2".
[0031] No. 1 Colloidal Solution
[0032] According to a first embodiment of the present invention, the colloidal solution is obtained by mixing:
[0033] - an inorganic precursor of said at least one TiO2;
[0034] - at least one C1-C4 alcohol;
[0035] -water;
[0036] - Catalysts for hydrolysis and condensation reactions.
[0037] The above components are mixed so that the inorganic precursor of TiO2 and water react in the presence of C1-C4 alcohol (forming a reaction solvent) and a catalyst to obtain the above colloidal solution.
[0038] Preferably, the C1-C4 alcohol is selected from methanol, ethanol, isopropanol, isobutanol, n-butanol, and mixtures thereof; preferably, the alcohol is ethanol.
[0039] Preferably, the amount by weight of C1-C4 alcohol is between 40% and 90%, more preferably between 50% and 80%, relative to the total weight of the components subjected to the sol-gel process.
[0040] Preferably, the amount by weight of water is between 1% and 20%, more preferably between 1% and 10%, relative to the total weight of the components subjected to the sol-gel process.
[0041] Preferably, the catalyst is an inorganic acid catalyst selected from HNO3, HCl and H2SO4, or, the catalyst is an organic acid catalyst, such as acetic acid. More preferably, the catalyst is an inorganic acid catalyst, even more preferably, the catalyst is HNO3. Preferably, the acid catalyst is added in an amount to obtain a pH between 2 and 3.5 or between 2 and 3, preferably an amount to obtain a pH of about 2.
[0042] Preferably, the molar ratio between the inorganic precursor of TiO2, the C1-C4 alcohol, water and the catalyst is 1:20-60:1-5:0.01-0.1, more preferably 1:40-60:2-3:0.02-0.05.
[0043] According to a preferred embodiment, the colloidal solution is obtained by mixing titanium n-butoxide (TNBT), ethanol, water and HNO3. Preferably, the colloidal solution is obtained by mixing titanium n-butoxide (TNBT), ethanol, water and HNO3 in a molar ratio of TNBT / ethanol / water / HNO3 equal to 1:50:2:0.04.
[0044] Preferably, the colloidal solution is obtained by mixing the above components (i.e., inorganic precursor of TiO2, C1-C4 alcohol, water and catalyst) at a temperature of at least 10°C and not higher than 50°C, preferably at room temperature. The term "room temperature" means a temperature between 18°C and 25°C.
[0045] Preferably, the step of mixing the above components is performed for a period of at least 15 hours, or for a period of at least 16 hours, or for a period of at least 17 hours, or for a period of at least 18 hours.
[0046] Preferably, said step of mixing the above components is performed for a period of between 18 and 24 hours, more preferably for a period of between 20 and 24 hours, even more preferably for a period of about 20 hours.
[0047] According to a preferred embodiment, the sol-gel process for obtaining said coating also comprises a heat treatment step after said step of applying the colloidal solution.
[0048] Preferably, the heat treatment step is performed at a temperature of at least 350°C, preferably at a temperature between 350°C and 500°C, more preferably at a temperature of about 400°C.
[0049] Preferably, the heat treatment step is performed for a time between about 30 minutes and 180 minutes, preferably for a time of about 1 hour.
[0050] Without being bound by theory, the drying and curing heat treatment steps allow for the elimination of the liquid phase in the gel, further promoting the coagulation phase.
[0051] No. 2 Colloidal Solution
[0052] According to a second embodiment of the present invention, the colloidal solution is obtained by mixing:
[0053] - an inorganic precursor of said at least one TiO2;
[0054] - at least one C1-C4 alcohol;
[0055] -water;
[0056] - A chelating agent, preferably, the chelating agent is acetylacetone.
[0057] The above components are mixed so that the inorganic precursor of TiO2 and water react in the presence of C1-C4 alcohol (forming a reaction solvent) and a chelating agent to obtain the above colloidal solution.
[0058] Preferably, the C1-C4 alcohol is selected from methanol, ethanol, isopropanol, isobutanol, n-butanol, and mixtures thereof; preferably, the alcohol is ethanol.
[0059] Preferably, the amount by weight of said at least one inorganic precursor of TiO 2 is between 4 and 35% by weight relative to the total weight of the components subjected to the sol-gel process.
[0060] Preferably, the amount by weight of C1-C4 alcohol is between 30% and 70% relative to the total weight of the components subjected to the sol-gel process.
[0061] Preferably, the amount by weight of water is between 1% and 55% relative to the total weight of the components subjected to the sol-gel process.
[0062] Preferably, the amount by weight of said chelating agent is between 1% and 10% relative to the total weight of the components subjected to the sol-gel process.
[0063] According to an embodiment of the present invention, the colloidal solution is obtained by mixing: titanium isopropoxide (TTIP) in an amount between 5% and 10% by weight, preferably in an amount of about 6% by weight; ethanol in an amount between 40% and 50% by weight, preferably in an amount of about 41% by weight; water in an amount between 50% and 60% by weight, preferably in an amount of about 51% by weight; and acetylacetone in an amount between 2% and 5% by weight, preferably in an amount of about 2% by weight.
[0064] According to another embodiment of the present invention, the colloidal solution is obtained by mixing: titanium isopropoxide (TTIP) in an amount between 25% and 30% by weight, preferably in an amount of about 30% by weight; ethanol in an amount between 60% and 70% by weight, preferably in an amount of about 65% by weight; water in an amount between 1% and 5% by weight, preferably in an amount of about 1.5% by weight; and acetylacetone in an amount between 7% and 10% by weight, preferably in an amount of about 9% by weight.
[0065] Preferably, the process for obtaining the above colloidal solution comprises: a first step of mixing an inorganic precursor of TiO2 with a C1-C4 alcohol; a subsequent step of adding a chelating agent and stirring the resulting solution for a time between about 10 minutes and 60 minutes, preferably stirring the resulting solution for a time of about 30 minutes; and a further step of adding water, preferably adding water dropwise, and stirring the resulting solution at room temperature for a time between about 30 minutes and 90 minutes, preferably stirring the resulting solution for a time of about 1 hour. The term "room temperature" is a temperature between 18°C and 25°C.
[0066] According to an embodiment, the method for obtaining the coating by applying the No. 2 colloid solution does not include a heat treatment step after the step of applying the colloid solution, unlike the process for obtaining the coating by applying the No. 1 colloid solution.
[0067] The following description relates to both a process for obtaining a coating layer including TiO 2 using colloidal solution No. 1 and a process for obtaining a coating layer including TiO 2 using colloidal solution No. 2.
[0068] The step of applying the above-mentioned colloidal solution on the metal substrate of the component according to the invention can be performed using various techniques selected from spray coating, dip coating, spin coating and electrodeposition.
[0069] According to a preferred embodiment, said step of applying the colloidal solution on the metal substrate of the component according to the invention is performed by dip coating.According to this embodiment, the metal substrate is immersed in the colloidal solution and withdrawn at a constant rate to allow the solvent to evaporate and to allow the solvent to gel.
[0070] The withdrawal speed of the metal substrate from the colloidal solution determines the thickness of the resulting coating. Preferably, the withdrawal speed of the metal substrate from the colloidal solution is at least 100 mm / min, or at least 150 mm / min, or at least 200 mm / min, or at least 250 mm / min. More preferably, the withdrawal speed of the metal substrate from the colloidal solution is greater than 250 mm / min, more preferably, the withdrawal speed of the metal substrate from the colloidal solution is between 300 mm / min and 1000 mm / min, for example, the withdrawal speed of the metal substrate from the colloidal solution is about 500 mm / min.
[0071] Preferably, the coating has a thickness of at least 50 nanometers. More preferably, the coating comprising TiO2 has a thickness between 1 micrometer and 5 micrometers, even more preferably, the coating comprising TiO2 has a thickness greater than 1 micrometer.
[0072] According to an embodiment, the metal substrate is aluminum or an aluminum alloy, for example, the metal substrate is an AlSix alloy, wherein x=5, 7, 9, 10, 11.
[0073] According to another embodiment, the metal substrate is iron or an iron alloy, for example, the metal substrate is steel or cast iron.
[0074] According to further embodiments, the metal substrate is titanium or a titanium alloy.
[0075] Optionally, the metal substrate is processed by a special treatment, for example, the metal substrate is processed by anodization.
[0076] In a preferred embodiment of the present invention, the component is a brake caliper of a brake system of a motor vehicle or a motorcycle, or the component is a part of the brake caliper.
[0077] In another embodiment, the component is a disc of a braking system of a car or motorcycle, or the component is a part of the disc, for example, the component is a bell of the disc.
[0078] Experimental Section
[0079] The colloidal solution was prepared as follows. Titanium n-butoxide (TNBT) was dissolved in ethanol; nitric acid and water were then added dropwise to the solution containing TNBT and ethanol while maintaining constant stirring; the resulting solution was stirred at room temperature for 20 hours. The molar ratio of TNBT, ethanol, water and nitric acid used was 1:50:2:0.04.
[0080] The solution is applied to an AlSi7 alloy substrate, for example of a brake caliper, by dip coating using a withdrawal speed of 500 mm / min.
[0081] Then, the brake caliper including the substrate thus coated was subjected to heat treatment at 400° C. for 1 hour, thereby obtaining a coating layer including TiO 2 having an anatase crystal phase.
[0082] The brake caliper obtained through the above-described process was subjected to the following test.
[0083] 1) Adhesion test
[0084] Perform cross-cut and tape tests in accordance with ASTM D3359 to determine the adhesion of the coating to the substrate. Figure 1 As is evident from the optical microscopy photographs shown in , the coating remained intact and therefore passed the adhesion test.
[0085] 2) Transparency
[0086] The transparency of the coating deposited on the substrate was verified by CIELAB or l*a*b colorimetric analysis to confirm the color difference between the coated substrate according to the invention and the corresponding uncoated substrate. The above test resulted in a value of ΔE=3, indicating that the color did not change significantly with respect to the uncoated substrate. The transparency level obtained is considered acceptable for applications in the automotive field.
[0087] 3) Contact angle
[0088] Static contact angle measurements were performed in accordance with standard UNI-828-2013 to determine the wettability behavior of the coating when deposited on an AlSi7 alloy substrate.
[0089] A contact angle of less than 10° was measured, ie 83° less than the corresponding uncoated substrate. This demonstrates the superhydrophilic behavior of the coated substrate according to the invention and thus the excellent antifouling properties of the coated substrate according to the invention.
[0090] 4) Photocatalytic activity
[0091] The photocatalytic activity was evaluated by monitoring the degradation of an organic dye (methylene blue) on the coated substrates according to the present invention and the corresponding uncoated substrates under ultraviolet irradiation. In particular, the photocatalytic performance was evaluated by monitoring the concentration of the organic dye over time with the aid of a UV-visible spectrophotometer.
[0092] It was observed that in the absence of light and photocatalyst, the dye did not degrade, indicating that no adsorption occurred on the surface of the substrate.
[0093] The stability of an organic dye (methylene blue) to UV light was also investigated in order to exclude the influence of dye photolysis on the photocatalytic activity results. In particular, a UV fluorescent lamp (6 W, 800 uW / cm 2 ) irradiated a solution of 16.5 μM methylene blue, with the UV fluorescent lamp placed 1 cm from the sample; the irradiation time was extended for 2 hours, so that measurements were taken every 15 minutes. It can be seen that the concentration of the dye dropped by only 2% after 2 hours of irradiation.
[0094] To investigate the photocatalytic activity of TiO2-based coatings on AlSi7 alloy substrates, an initial solution of 16.5 μM methylene blue was prepared in which the coated samples were immersed. The photocatalytic activity was investigated using two UV fluorescent lamps (6 W, 800 uW / cm 2 ) irradiated the reaction medium, and the UV fluorescent lamp was placed 1 cm away from the sample. The photocatalytic process was monitored by tracking the decrease in the adsorption intensity of the dye at 662 nm with the irradiation time. The irradiation time was extended for 2 hours, so that the UV-visible spectrophotometer was measured every 15 minutes. The results obtained are Figure 2 The graph in Figure 5 shows the degradation of the methylene blue dye on a coated substrate over time compared to the degradation of the same dye on an uncoated substrate. The degradation over time is expressed as a percentage of degradation over time, or as a degradation rate. It should be noted that on the uncoated substrate, no degradation of the dye occurred, while on the coated substrate according to the invention, the degradation percentage was 18%, demonstrating the photocatalytic activity of the TiO2-based coating.
[0095] 5) Sand adhesion test
[0096] A protocol has been developed to quantify the self-cleaning qualities of TiO2-based coatings, in particular the adhesion of sand to coated substrates according to the invention and to corresponding uncoated reference substrates.
[0097] The sand was dropped onto the substrate through a funnel. The distance between the funnel and the substrate was 15 cm, and the amount of sand dropped onto the substrate was 25 g.
[0098] The size distribution of the sand used for this test was less than 250 microns.
[0099] In order to perform the above test, two inclined planes are used, in this example, a plane with an inclination of 20° and a plane with an inclination of 40°.
[0100] The amount of sand remaining attached to the substrate was determined by the difference in weight of the substrate before and after the test. Specifically, the fouling rate percentage of the uncoated substrate was set to 100, and a proportional calculation was performed to determine the fouling rate percentage of the coated substrate.
[0101] The results obtained using a 20° inclined plane are shown in Table 1 below, while the results obtained using a 40° inclined plane are shown in Table 2 below.
[0102]
[0103] Table 1
[0104]
[0105] Table 2
[0106] As can be seen from the results reported in the table above, on the uncoated reference substrate the adhesion of the sand is high (100% fouling by weight), whereas on the coated substrates according to the invention the fouling is low.
[0107] It can be further seen from the above results that as the inclination of the plane increases, the adhesion of the sand decreases (for a 20° inclined plane, the dirt rate by weight is 53.03030%, and for a 40° inclined plane, the dirt rate by weight is 12.3265306%).
[0108] 6) Soil adhesion test
[0109] The soil adhesion test was performed following the same protocol as the sand adhesion test, i.e. the soil adhesion test was performed by dropping soil drops (i.e. drops of water mixed with sand) on the coated substrates according to the present invention and on the corresponding uncoated substrates.
[0110] The same behavior was found, ie the adhesion of soil droplets on the coated substrates according to the invention was lower.
[0111] Obviously, the described embodiments are only specific embodiments of the invention. A person skilled in the art will be able to make all necessary modifications to the components and methods of the invention to adapt them to the particular situation without departing from the scope of protection as defined in the appended claims.
Claims
1. A component of an automobile or motorcycle, comprising a metal substrate and a coating for the substrate, wherein: said coating comprises TiO2 and can be obtained by a sol-gel process comprising the step of applying a colloidal solution on said metal substrate of said part of the car or motorcycle, The colloidal solution is obtained by hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water. The inorganic precursor of TiO2 has a molecular formula Ti(X)4, wherein the X group is a hydrolyzable group selected from halogen, -OR alkoxy group and -COOR acyloxy group, and the X groups are the same or different from each other, wherein R is preferably a C1-C6 alkyl group.
2. The component according to claim 1, wherein The inorganic precursor of TiO2 is titanium n-butoxide (TNBT) or titanium isopropoxide (TTIP).
3. A component according to claim 1 or 2, wherein: The colloidal solution is obtained by mixing: - at least one inorganic precursor of said TiO2; - at least one C1-C4 alcohol, preferably, the C1-C4 alcohol is ethanol; -water; - a catalyst for the hydrolysis and condensation reactions, preferably, the catalyst is an inorganic acid catalyst selected from HNO3, HCl and H2SO4.
4. The component according to claim 3, wherein The molar ratio between the inorganic precursor of TiO2, the C1-C4 alcohol, water and the inorganic acid catalyst is 1:20-60:1-5:0.01-0.
1.
5. A component according to claim 3 or 4, wherein: The colloidal solution is obtained by mixing TNBT, ethanol, water and HNO3. Preferably, the colloidal solution is obtained by mixing TNBT, ethanol, water and HNO3 in a molar ratio of TNBT / ethanol / water / HNO3 equal to 1:50:2:0.
04.
6. A component according to any one of claims 3 to 5, wherein Said coating can be obtained by a process further comprising: a heat treatment step after said step of applying said colloidal solution.
7. The component according to claim 6, wherein The heat treatment step is performed at a temperature of at least 350°C; preferably, the heat treatment step is performed at a temperature between 350°C and 500°C; more preferably, the heat treatment step is performed at a temperature of about 400°C; preferably, the heat treatment step is performed at a temperature of at least 350°C for a time between about 30 minutes and 180 minutes, for example, the heat treatment step is performed at a temperature of at least 350°C for a time of about one hour; preferably, the heat treatment step is performed at a temperature between 350°C and 500°C for a time between about 30 minutes and 180 minutes, for example, the heat treatment step is performed at a temperature between 350°C and 500°C for a time of about one hour; preferably, the heat treatment step is performed at a temperature of about 400°C for a time between about 30 minutes and 180 minutes, for example, the heat treatment step is performed at a temperature of about 400°C for a time of about 1 hour.
8. The component according to claim 1 or 2, wherein: The colloidal solution is obtained by mixing: - at least one inorganic precursor of said TiO2; - at least one C1-C4 alcohol, preferably, the C1-C4 alcohol is ethanol; -water; - A chelating agent, preferably, the chelating agent is acetylacetone.
9. The component according to claim 8, wherein The colloidal solution is obtained by mixing: an amount between 4% and 35% by weight of at least one inorganic precursor of said TiO2, at least one of said C1-C4 alcohols in an amount between 30% and 70% by weight; Water in an amount between 1% and 55% by weight; an amount between 1% and 10% by weight of said chelating agent; The percentage amounts are relative to the total weight of the components subjected to the sol-gel process.
10. A component according to claim 8 or 9, wherein The colloidal solution is obtained by mixing: between 5% and 10% by weight of TTIP; between 40% and 50% by weight of ethanol; between 50% and 60% by weight of water; between 2% and 5% by weight of acetylacetone.
11. A component according to claim 8 or 9, wherein: The colloidal solution is obtained by mixing: between 25% and 30% by weight of TTIP; between 60% and 70% by weight of ethanol; between 1% and 5% by weight of water; between 7% and 10% by weight of acetylacetone.
12. A component according to any one of the preceding claims, wherein The step of applying the colloidal solution on the metal substrate is performed by dipping the metal substrate into the colloidal solution.
13. The component according to claim 12, wherein The metal substrate is extracted from the colloidal solution at a speed higher than 250 mm / min. Preferably, the metal substrate is extracted from the colloidal solution at a speed between 300 mm / min and 1000 mm / min. More preferably, the metal substrate is extracted from the colloidal solution at a speed of about 500 mm / min.
14. A component according to any one of the preceding claims, wherein The coating has a thickness between 1 micron and 5 microns, preferably, the coating has a thickness greater than 1 micron.
15. A component according to any one of the preceding claims, wherein The substrate is made of aluminum or an aluminum alloy; or, the substrate is made of iron or an iron alloy, for example, the substrate is made of steel or cast iron; or, the substrate is made of titanium or a titanium alloy.
16. A component according to any one of the preceding claims, the component being a brake caliper of a braking system of a motor vehicle or a motorcycle, or the component being part of a brake caliper of a braking system of a motor vehicle or a motorcycle, or The component is a brake disc of a braking system of a motor vehicle or a motorcycle, or the component is a part of a brake disc of a braking system of a motor vehicle or a motorcycle, for example, the component is a bell of the disc.
17. A method for producing a component for a motor vehicle or motorcycle according to any one of the preceding claims, the method comprising the steps of: Providing a component including a metal substrate for an automobile or a motorcycle, applying a colloidal solution obtained by hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water to the metal substrate, The inorganic precursor of TiO2 has a molecular formula Ti(X)4, wherein the X group is a hydrolyzable group selected from halogen, -OR alkoxy group and -COOR acyloxy group, and the X groups are the same or different from each other, wherein R is preferably a C1-C6 alkyl group, Preferably, the metal substrate is made of aluminum or an aluminum alloy; or, the metal substrate is made of iron or an iron alloy, for example, the metal substrate is made of steel or cast iron; or, the metal substrate is made of titanium or a titanium alloy.
18. The method according to claim 17, wherein: The colloidal solution is applied to the metal substrate by dipping the metal substrate into the colloidal solution. Preferably, the metal substrate is extracted from the colloidal solution at a speed higher than 250 mm / min. Preferably, the metal substrate is extracted from the colloidal solution at a speed between 300 mm / min and 1000 mm / min. More preferably, the metal substrate is extracted from the colloidal solution at a speed of about 500 mm / min.
19. Use of a coating obtainable by the method according to claim 17 or 18 for providing self-cleaning properties to a metal substrate to which the coating is applied, in particular, The coating is used to provide self-cleaning properties to a metal substrate of a component of an automobile or motorcycle, Preferably, the substrate is made of aluminum or an aluminum alloy; or, the substrate is made of iron or an iron alloy, for example, the substrate is made of steel or cast iron; or, the substrate is made of titanium or a titanium alloy.
20. The use according to claim 19, wherein The coating has a thickness between 1 micron and 5 microns, preferably, the coating has a thickness greater than 1 micron.
21. Use of a colloidal solution as a coating for a metal substrate, the colloidal solution being used to provide the coating with self-cleaning properties, in particular, the coating for the metal substrate is a coating for a metal substrate of a component of an automobile or a motorcycle, The colloidal solution is obtained by hydrolysis and condensation reaction between an inorganic precursor of TiO2 and water. The inorganic precursor of TiO2 has a molecular formula of Ti(X)4, wherein The X group is a hydrolyzable group selected from halogen, -OR alkoxy group and -COOR acyloxy group, and the X groups are the same or different from each other, wherein R is preferably a C1-C6 alkyl group, Preferably, the inorganic precursor of TiO2 is titanium n-butoxide (TNBT) or titanium isopropoxide (TTIP).
22. The use according to claim 21, wherein The colloidal solution is obtained by mixing: - at least one inorganic precursor of said TiO2; - at least one C1-C4 alcohol, preferably, the C1-C4 alcohol is ethanol; -water; - a catalyst for the hydrolysis and condensation reactions, preferably, the catalyst is an inorganic acid catalyst selected from HNO3, HCl and H2SO4.
23. The use according to claim 22, wherein The molar ratio between the inorganic precursor of TiO2, the C1-C4 alcohol, water and the inorganic acid catalyst is 1:20-60:1-5:0.01-0.
1.
24. The use according to claim 22 or 23, wherein The colloidal solution is obtained by mixing TNBT, ethanol, water and HNO3. Preferably, the colloidal solution is obtained by mixing TNBT, ethanol, water and HNO3 in a molar ratio of TNBT / ethanol / water / HNO3 equal to 1:50:2:0.
04.
25. The use according to claim 21, wherein The colloidal solution is obtained by mixing: - at least one inorganic precursor of said TiO2; - at least one C1-C4 alcohol, preferably, the at least one C1-C4 alcohol is ethanol; -water; - A chelating agent, preferably, the chelating agent is acetylacetone.
26. The use according to claim 25, wherein The colloidal solution is obtained by mixing: an amount between 4% and 35% by weight of at least one inorganic precursor of said TiO2, at least one of said C1-C4 alcohols in an amount between 30% and 70% by weight; Water in an amount between 1% and 55% by weight; an amount between 1% and 10% by weight of said chelating agent; The percentage amounts are relative to the total weight of the components subjected to the sol-gel process.